Targeting Loxosceles spider Sphingomyelinase D with small-molecule inhibitors as a potential therapeutic approach for loxoscelism. (1st January 2019) - Lopes, Priscila Hess; Murakami, Mário T.; Portaro, Fernanda C. V.; Mesquita Pasqualoto, Kerly Fernanda; van den Berg, Carmen; Tambourgi, Denise V.
Abstract: Loxosceles spiders' venoms consist of a mixture of proteins, including the sphingomyelinases D (SMases D), which are the main toxic components responsible for local and systemic effects in human envenomation. Herein, based on the structural information of SMase D from Loxosceles laeta spider venom and virtual docking-based screening approach, three benzene sulphonate compounds (named 1, 5 and 6) were identified as potential Loxosceles SMase D inhibitors. All compounds inhibited the hydrolysis of the sphingomyelin substrate by both recombinant and native SMases D. Compounds 5 and 6 acted as SMases D uncompetitive inhibitors with Ki values of 0.49 µM and 0.59 µM, respectively. Compound 1 is a mixed type inhibitor, and presented a Ki value of 0.54 µM. In addition, the three compounds inhibited the binding of SMases D to human erythrocytes and the removal of glycophorin C from the cell surface, which are important events in the complement-dependent haemolysis induced by Loxosceles venom. Moreover, compounds 5 and 6 reduced the binding of SMases to human keratinocytes membrane and the venom induced cell death. Importantly, compounds 5 and 6 also controlled the development of the necrotic lesion in an in vivo model of loxoscelism. Together, our findings indicate that the novel SMase D inhibitors presented here are able to suppress both local and systemic reactions induced by Loxosceles venoms. Since the number of Loxosceles envenomation accidents is currently growing worldwide, our results indicate that both inhibitors are promising scaffolds for the rational design of new drugs targeting SMases D from these spiders.